Biofilms in hoses utilized to divert colostrum and milk on dairy farms: A report exploring their potential role in herd health, milk quality, and public health - Latorre, Alejandra A.; Oliva, Ricardo; Pugin, Julio; Estay, Alexis; Nualart, Francisco; Salazar, Katterine; Garrido, Natacha; Muñoz, Marcos A. (Frontiers in Veterinary Science, 2022)
Biofilms in milking equipment on dairy farms have been associated with failures in cleaning and sanitizing protocols. These biofilms on milking equipment can be a source of contamination for bulk tank milk and a concern for animal and public health, as biofilms can become on-farm reservoirs for pathogenic bacteria that cause disease in cows and humans. This report describes a cross-sectional study on 3 dairy farms, where hoses used to divert waste milk, transition milk, and colostrum were analyzed by culture methods and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) to assess the presence of pathogenic bacteria such as Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella spp. In addition, the presence of biofilms was analyzed using scanning electron microscopy and confocal spectral microscopy. Biofilms composed of multispecies microbial communities were observed on the surfaces of all milk hoses. In two dairy farms, S. aureus, P. aeruginosa, Klebsiella pneumoniae, and Klebsiella oxytoca were isolated from the milk hose samples collected. Cleaning and sanitation protocols of all surfaces in contact with milk or colostrum are crucial. Hoses used to collect waste milk, colostrum, and transition milk can be a source of biofilms and hence pathogenic bacteria. Waste milk used to feed calves can constitute a biosecurity issue and a source of pathogens, therefore an increased exposure and threat for the whole herd health and, potentially, for human health.